Rancang Bangun Sistem Monitoring Arduino yang Terintegrasi SCADA dan Basis Data Menggunakan Metode Komunikasi Serial - Berza H. Sanjaya; Ardi Pujiyanta; Riky Dwi Puriyanto (SKANIKA: Sistem Komputer dan Teknik Informatika, 2025)
Monitoring systems are very important in daily life for storing data permanently, not just temporarily. Many previous studies did not save data into databases, resulting in data loss after some time. With technological advancements, innovations have emerged that allow for large-capacity data storage and retrieval even after long periods. The Arduino microcontroller, especially the Arduino UNO R3, has limited storage capacity and cannot display processed variable values. Therefore, an alternative solution is needed to store and display this data. This research develops a monitoring system for analog input on the Arduino UNO R3 with a 0-5 VDC signal that sends data serially to AVEVA Edge SCADA. SCADA functions as an interface to display the data and transfer it to a MySQL database. Testing results show that the system performs well, can display data via SCADA, and saves it comprehensively in MySQL with configurable sampling times. Ten tests yielded 100% accuracy and 0% error, proving that this system is reliable and effective for monitoring analog data using Arduino and SCADA